Prevalence of malocclusion and orthodontic treatment needs among 12-15 years old school children of Udaipur, India - Tak, Mridula; Nagarajappa, Ramesh; Sharda, Archana J; Asawa, Kailash; Tak, Aniruddh; Jalihal, Sagar; Kakatkar, Gauri (European Journal of Dentistry, 2013)
Objective: The objective of the study is to assess the prevalence of malocclusion and orthodontic treatment needs among 12-15 years old school children of Udaipur, India. Materials and Methods: A cross-sectional descriptive survey was conducted among 887 subjects aged 12-15 years. The prevalence of malocclusion and orthodontic treatment needs was assessed using dental aesthetic index (World Health Organization, 1997). General information on demographic data was also recorded. Chi-square test, analysis of variance and Scheffe′s test were employed for statistical analysis. Results: Malocclusion and orthodontic treatment need was reported among 33.3% of the study subjects. A significant age and gender difference depicting preponderance among younger age group and a male proclivity was experiential. A significant improvement in anterior crowding and largest anterior maxillary irregularity with age was documented. Males had a significantly higher prevalence of anterior crowding, midline diastema and largest anterior maxillary irregularity than females. Conclusions: The prevalence of malocclusion and orthodontic treatment needs among school children of Udaipur city, Rajasthan, India was found to be 33.3%.A significant age and gender difference was observed in prevalence of malocclusion, crowding and largest anterior maxillary irregularity. Midline diastema showed a significant gender difference. The baseline information outlined in the present study can be appropriately utilized for the future planning to meet the orthodontic treatment need among the population.
Keywords: Child; India; malocclusion; prevalence